Asymmetric effect of real exchange rate risk on foreign direct investment: Empirical evidence in ASEAN-4 - Jaratin Lily; Mori Kogid; Dullah Mulok; Rozilee Asid (2020)
This study investigates the asymmetric effect of exchange rate risk (volatility) on the real foreign direct investment (FDI) inflows in Malaysia, the Philippines, Singapore, and Thailand (ASEAN-4) using the Nonlinear Autoregressive Distributed Lag (NARDL) model. The results revealed the occurrence of a long-run asymmetric cointegration between real FDI inflows and real exchange rate risk in the Philippines, Singapore, and Thailand, but not in Malaysia. For the Philippines and Singapore, there is evidence of long-run asymmetry whereas short-run asymmetry exists for the case of Thailand. These findings imply that the asymmetric effects prove to be useful in providing essential information to the related parties on how FDI inflows react to exchange rate risks differently. Therefore, policymakers in ASEAN countries should be concerned about the asymmetric effect of the exchange rate volatility to mitigate the stylized effects of exchange rate movements on FDI inflows.